Tobacco RhoGTPase ACTIVATING PROTEIN1 spatially restricts signaling of RAC/Rop to the apex of pollen tubes - Klahre, Ulrich; Kost, Benedikt (The Plant Cell, 2006)
Regulation by Rho-type small GTPases, such as RAC5, is important for the maintenance of polarity in tobacco (Nicotiana tabacum) pollen tubes. We previously showed that RhoGDI2 is necessary for RAC5 localization. Here, we describe the GTPase activating protein RhoGAP1 that controls the area of RAC5 activity. RhoGAP1 N-terminal and CRIB (for Cdc42/Rac-interactive binding) domains are both necessary for targeting yellow fluorescent protein-RhoGAP1 fusions to the plasma membrane close to, but not in, pollen tube apices. We propose that this localization restricts apical Rho-type GTPase activity from spreading toward the flanks, which ensures the maintenance of RAC signaling at the apex. The CRIB domain is not required but enhances in vitro RhoGAP1 activity toward the pollen tube-specific-RAC5. A mutation reducing GAP activity of RhoGAP1 leads to ballooning pollen tubes resembling those overexpressing RAC5. To ascertain the specific targeting mechanism of RhoGAP1, we isolated a 14-3-3 protein interacting with RhoGAP1. When overexpressed with RhoGAP1, it counteracts the growth-retarding effect of RhoGAP1 overexpression and attenuates RhoGAP1 membrane localization but, overexpressed alone, induces only small architectural changes. We propose that inactivation of RAC5 by the subapically localized RhoGAP1, together with dynamic relocalization of inactivated RAC5 from flanks to tip by RhoGDI2, leads to spatial restriction of RAC5 to pollen tube apices, thereby sustaining polar growth.